1999
DOI: 10.1159/000020942
|View full text |Cite
|
Sign up to set email alerts
|

Improved Specificity of NRBC Detection in Chorionic Villus Sample Supernatant Fluids Using Anti-Zeta and Anti-Epsilon Monoclonal Antibodies

Abstract: Objective: Fetal erythrocytes leak from fetal capillaries at the time of chorionic villus sampling (CVS). It has been reported that in approximately 60% of CVS cases fetal nucleated red blood cells (NRBC) can be isolated from the supernatant fluid by immunophenotyping with monoclonal antibody (Ab) against the γ-chain of fetal hemoglobin and used as an additional source for confirmation of the fetal karyotype. However, the increased prevalence of β-thalassemia mutations in countries such as Greece results in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
4
9
0
1
Order By: Relevance
“…In agreement with results of previous studies [11][12][13][14][15], we found that gamma hemoglobin positive NRBCs were present in all and that epsilon hemoglobin positive NRBCs were present in almost all fetal blood samples from gestation weeks 12-20. It is noteworthy that epsilon hemoglobin positive cells were present in a sample as late as 20 weeks.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with results of previous studies [11][12][13][14][15], we found that gamma hemoglobin positive NRBCs were present in all and that epsilon hemoglobin positive NRBCs were present in almost all fetal blood samples from gestation weeks 12-20. It is noteworthy that epsilon hemoglobin positive cells were present in a sample as late as 20 weeks.…”
Section: Discussionsupporting
confidence: 93%
“…Secondly, the gamma marker is not fully fetus specific, a finding that is in accordance with our previous finding using the mRNA for gamma hemoglobin as marker, where we found a few percent of the gamma hemoglobin positive cells to be maternal [to be published]. Others have made similar findings [12][13][14].…”
Section: Post-cvs Maternal Samples: Specificity Of Gamma and Epsilon supporting
confidence: 92%
See 1 more Smart Citation
“…There may be a case for using ␥-globin for sorting, favoring yield over purity, but it is not nearly specific enough for accurate fetal erythroblast identification because of increased maternal fetal hemoglobin production in pregnancy 5 and ␤ thalassemia. 6,7 In contrast, ⑀-or -globin chains appear specific for fetal cells in chorionic villus supernatants 7 but have not been tested in maternal blood. Whereas -globin is occasionally produced in adults with ␣ thalassemia, 8 ⑀-globin has not been found in adult peripheral blood, 9 making it the preferred fetal cell identifier.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study we demonstrated that anti-hemoglobin-Â antibody is more specific than anti-hemoglobin-Á in detecting fetal NRBCs in chorionic villus sampling (CVS) washings [10]. Choolani et al [11] confirmed the specificity of anti-hemoglobin-Â for fetal NRBCs in mixtures of male fetal erythroblasts with female adult bone marrow erythroblasts.…”
Section: Introductionmentioning
confidence: 93%